Предмет: Алгебра,
автор: Metuh
упростите выражение 2 sin в квадрате(Π/6-a)+6-2 cos в квадрате (Π/6-a)
Ответы
Автор ответа:
0
2(sin²(π/6-a)-cos²(π/6-a)+6=-2cos(π/3-2a)+6=
=-2(cosπ/3cos2a+sinπ/3sin2a)+6=-2(1/2*cos2a+√3/2sin2a)+6=
=-cos2a-√3sin2a+6
=-2(cosπ/3cos2a+sinπ/3sin2a)+6=-2(1/2*cos2a+√3/2sin2a)+6=
=-cos2a-√3sin2a+6
Похожие вопросы
Предмет: Русский язык,
автор: tamerlangaliullin30
Предмет: Биология,
автор: pridvorova333
Предмет: Литература,
автор: melanab
Предмет: Биология,
автор: polinka44
Предмет: Биология,
автор: kirill2001902